Haptoglobin increases with age in rat hippocampus and modulates Apolipoprotein E mediated cholesterol trafficking in neuroblastoma cell lines - Spagnuolo, Maria Stefania; Maresca, Bernardetta; Mollica, Maria Pina; Cavaliere, Gina; Cefaliello, Carolina; Trinchese, Giovanna; Esposito, Maria Grazia; Scudiero, Rosaria; Crispino, Marianna; Abrescia, Paolo; Cigliano, Luisa (Frontiers in Cellular Neuroscience, 2014)
Alteration in cholesterol metabolism has been implicated in the pathogenesis of several neurodegenerative disorders. Apolipoprotein E (ApoE) is the major component of brain lipoproteins supporting cholesterol transport. We previously reported that the acute-phase protein Haptoglobin (Hpt) binds ApoE, and influences its function in blood cholesterol homeostasis. Major aim of this study was to investigate whether Hpt influences the mechanisms by which cholesterol is shuttled from astrocytes to neurons. In detail it was studied Hpt effect on ApoE-dependent cholesterol efflux from astrocytes and ApoE-mediated cholesterol incorporation in neurons. We report here that Hpt impairs ApoE-mediated cholesterol uptake in human neuroblastoma cell line SH-SY5Y, and limits the toxicity of a massive concentration of cholesterol for these cells, while it does not affect cholesterol efflux from the human glioblastoma-astrocytoma cell line U-87 MG. As aging is the most important nongenetic risk factor for various neurodegenerative disorders, and our results suggest that Hpt modulates ApoE functions, we evaluated the Hpt and ApoE expression profiles in cerebral cortex and hippocampus of adolescent (2 months), adult (5 and 8 months), and middle-aged (16 months) rats. Hpt mRNA level was higher in hippocampus of 8 and 16 month-old than in 2-month old rats (p<0.05), and Hpt concentration increased with the age from adolescence to middle-age (p<0.001). ApoE concentration, in hippocampus, was higher (p<0.001) in 5 month-old rats compared to 2 month but did not further change with aging. No age-related changes of Hpt (protein and mRNA) were found in the cortex. Our results suggest that aging is associated with changes, particularly in the hippocampus, in the Hpt/ApoE ratio. Age-related changes in the concentration of Hpt were also found in human cerebrospinal fluids.The age-related changes might affect neuronal function and survival in brain, and have important implications in brain pathophys